Prognostic Factors of Early Neonatal Sepsis in the City of Cartagena Colombia (2018)
Introduction: The obstetirc or noenatal risk factors, are in many cases the major evidence to define and forecast of an early neonatal sepsis, considering that a newborn that has lived less tan 72 hours presents unspecified clinical manifestations and the diagnostic exams utilize infectious and inflammatory markers, with there being very litttle scientific evidence to support and establish an early diagnosis. Objective: Associate the obstetric and neonatal risk factors with the presence of early sepsis in Cartagena. Materials and Methods: A retrospective study of cases and controls was conducted. The sample consisted of 183 cases and 366 controls, including pacients who met simultaneously inclusion and exclusion criteria. A bivariated analysis and a multivariated model of regression logistics were used. Results: Among the associtated variables and early sepsis in which it was able to define the risk that is found when there is a premature membrane rupture > 18 hours (OR 9,57 IC 95% 4,12-22,26), premature newborn (OR 8,19 IC 95% 3,66-18,3), the presence of maternal fever (OR 6,49 IC 95% 3,43-12,3), marital status (OR 5,89 IC 95% 3,42-10,15) and level of education (OR 4,80 IC 95% 2,63-8,77). Conclusions: The mechanisms of fetal evaluation and maternal prophylaxis should be prioritized in the cases of pregnant women that present a premature membrane rupture >18 hours, and have kids who were born premature and living in couple with a low level of education.